Elements of the Buddhist Medical System - Divino, Federico (History of Science in South Asia)

(untitled) (University of Alberta Library, 2023)
This article aims to explore the anthropological foundations of early Buddhist medical thought by conducting a comprehensive analysis of Pāli texts and their relationship to the development of Indian traditional medicine, such as Āyurveda. The research investigates the possible existence of an ancient Buddhist medical system and compares it with contemporary medical systems, such as Hippocratic medicine. By examining the Bhesajjakkhandhaka and the Bhesajjamañjūsā, two Pāli texts that discuss medicine, the article seeks to outline the key elements of ancient Buddhist medical conceptions. Furthermore, it emphasizes the importance of understanding the evolution of Buddhist medical practices and their potential role in defining Indian traditional medicine. The findings could provide a foundation for historians of Indian medicine to delve into even more complex aspects of the medical tradition in ancient Buddhism.